Pinch analysis of Nynas refinery - an energy efficiency study - Gunnarsson, Anna; Magnusson, Carin (My University, 2011)
Energy efficiency is one of many ways to reduce the problems of releasing more greenhouse gases into the atmosphere. The potential for energy savings due to energy efficiency measures can be large in industrial processes, especially in energy intensive businesses such as the refinery industry. In this project the oil refinery Nynas AB, situated near the harbour in Gothenburg, is studied. The plant is specialized in producing bitumen and naphthenic oils, mainly for the Nordic market. The objective of this thesis is to investigate opportunities to increase process energy efficiency at the refinery Nynas AB. The main aim of the project is to locate energy savings by use of pinch analysis and to evaluate these. The primary focus of this study is the distillation section of the plant due to its large energy usage, 60 % of the total energy demand at the plant. Within the distillation area two distillation columns and a furnace are located. The present energy demand in this area is 6.5 MW of heating and 5.0 MW of cooling. The results of the pinch analysis indicate that the theoretical minimum energy demand for the plant is 3.7 MW heating and 3.1 MW cooling. This implies that there is a potential for savings of around 42 % for heating and 37 % for cooling. However a more advanced analysis of the plant indicates that it is complicated to retrofit, thus reaching these energy targets is not reasonable from an economic perspective. The focus of the study was therefore on identifying measures that save energy without attempting to reach the maximum energy savings target. Two retrofit suggestions was performed which both added a new heat exchanger to the heat exchanger train preheating crude oil with bitumen at the plant. The placement of the additional heat exchanger is different in the retrofit suggestions and gives different advantages concerning material, wear and size. The suggestions both decrease the energy demand in the furnace by 24 % and reduce about 55 % of the pinch violations. It would also decrease the CO2 emissions by 7000 tonnes/yr due to reduced fuel demand. In both retrofit suggestions the steam generator producing 2 barg steam to preheat the feedwater was reduced. This was solved by utilizing the excess heat below the pinch to preheat the fresh water. Finally retrofit suggestion 1 with a new heat exchanger close to the furnace, using an appropriate construction material was recommended. This retrofit option was considered to protect of the existing heat exchangers. An economic analysis of retrofit options 1 and 2 showed a payback period corresponding to about 9 months for retrofit 1 and 18 months for retrofit 2. The conclusion is that further heat exchange in the process is something to recommend.
Keywords: Energi; Innovation och entreprenörskap (nyttiggörande); Kemiska processer; Energy; Innovation & Entrepreneurship; Chemical Process Engineering